Pengaruh Music Therapy Terhadap Penurunan Hiperaktivitas Pada Anak Dengan Gangguan Attention Deficit Hyperactivity Disorder (ADHD): Literature Review - Putri, Nahda Tiramika; Asthiningsih, Ni Wayan Wiwin; Milkhatun, Milkhatun (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background: Attention Deficit Hyperactivity Disorder (ADHD) It exhibits symptoms of impulsivity, hyperactivity, and inattention, and is a mental disorder. The use of music in therapy can help people with a variety of social, emotional, behavioral, cognitive, and motor problems. When using music for therapeutic purposes, music therapy can specifically change how the brain works by training it to function differently.Objective: to find out if music therapy might help youngsters with ADHD who are too hyperactive to focus on tasks at hand.Methods: In this research, the method used is a literature review, with scholarly journal articles sourced online serving as the primary source material. There are a total of fifteen journal; eleven of them are international journals and four are national ones. Results: This study found that children with ADHD had less hyperactivity after receiving music therapy, according to a review of 15 periodicals. Conclusion: One of the therapeutic options to calm children's hyperactivity is music therapy, Attention Deficit Hyperactivity Disorder (ADHD)